Drinking water and health assessment in a Northern Arizona community. Issue 1 (1st February 2023) - Cooksey, Emily; Verhougstraete, Marc; Sneed, Sam J.; Joseph, Carrie Nuva; Blohem, Jonathan; Paukgana, Morris; Joshweseoma, Lori; Sehongva, Gregory; Hadeed, Steven; Harris, Robin; O'Rourke, Mary Kay
Abstract: Arizona is a mineral rich state that relies on a mix of surface and ground water supplies for drinking water requirements. Small, rural water systems relying on groundwater frequently encounter elevated metal(loid) measures, particularly inorganic arsenic (As +3, +5 ). Such contaminant occurrences can be associated with adverse health outcomes including cancers. The Hopi Environmental Health Project examined drinking water quality and water consumption behaviors from 76 homes on Hopi lands over a four-year period. Water samples were analyzed for 28 elements and compared to US Environmental Protection Agengy (EPA) maximum contaminant levels (MCL). Only municipal/piped water had a mean arsenic concentration (11.01 µg/L) exceeding the MCL (10.0 µg/L). All other water types and elements occurred below MCL when detected. A lifetime cancer and hazard quotient associated with arsenic consumption through each water type was performed and piped/municipal water was found to carry the greatest risks (9.96 cases per 10, 000 people). Results from this study showed the potential for multiple contaminants to be present in drinking water from Hopi lands and the need for further health assessment of routine exposure to low doses of contaminant mixtures through drinking water.